Occupational therapy for adults with intellectual disabilities and sensory processing challenges: a Delphi study exploring practice within acute assessment and treatment units. Issue 1 (6th May 2021) - Justice, Helen; Haines, David; Wright, Jon
Abstract : Purpose: Lack of research means guidance regarding the most effective sensory interventions for adults with intellectual disabilities is limited. Preliminary consensus evidence was created by gathering experienced occupational therapists' views on practice. The purpose of this study was to establish important elements of practice when using sensory integration-informed approaches on assessment and treatment units. Design/methodology/approach: A modified Delphi process was used to gather, explore and synthesise the views of 13 occupational therapists. Data was collected via online surveys and included quantitative importance ratings and qualitative comments. Findings: An experienced panel was in strong agreement regarding many elements of practice they felt were important for use in this setting, and a list of important practice items was created. Two themes were identified: "Complexity" and "Pragmatism vs. Ideal World." The themes highlight challenges to practice in this area and the complex clinical reasoning used to overcome these. Research limitations/implications: Participants disagreed about the level of importance of a substantial number of items, therefore items that did not reach consensus may still be important. Practical implications: This study indicates potentially helpful clinical tools, facilities and training and identifies support needed for occupational therapists working in these settings. Originality/value: This study contributes to the body of knowledge regarding how occupational therapists do and could work with people with intellectual disabilities and sensory integration difficulties. Although this study takes a UK and Ireland perspective, similar agendas regarding care and support for those with intellectual disabilities internationally mean findings are relevant more widely.